THE EFFECTIVENESS OF STUDENT INTERVENTION PROGRAM - MY ADVISEE PROGRAM OUTCOMES (PO) - Syed Muhammad Bin Syed Yahya,; Nurul Farraheeda Binti Abdul Rahman,; Nurul Ain Umaiban Binti Yusof,; Azyan Zafyrah Binti Mohd Zahid, (Journal of Islamic, Social, Economics and Development, 2021)
The Faculty concerns about the performance of the program outcomes (PO) ofDiploma Student in Civil Engineering. Therefore, ‘My Advisee POs’ is carried out everysemester to the students that have less than 50% of their PO attainment in the previous semesterwhich is after completing the fundamental and intermediate courses of the examination result.Involvement of the Lecturer in Charged (LIC), Team Teaching, and Academic Advisor (AA) ismonitored closely by the Head of Studies and Outcome-Based Education (OBE) Committee toensure the program is successful and improvement of the PO is visible. The LIC and TeamTeaching are responsible for selecting and conducting one or half-day programs such asseminar/ webinar/ technical talk/ simulation/ competition subjected to their PO. In sessionswith the AA, students will receive guidance and support through the offer of appropriate adviceincluding referral to appropriate support systems, e.g., learning support program, onlineresources, counselling, referral to relevant academic or administrative points of contact, suchas Buddy System Coordinator, Academic and Student Affair and extra tutorial support from theFaculty’s intervention program. This paper describes a survey tool, called the ProgramEffectiveness Survey, which can be used to evaluate and improve the effectiveness of theprogram. The tool provides feedback from students on the outcomes and understanding of thevirtual webinar programs and how it could be improved. The survey was found to have arelatively high percentage, but reliability was below appropriate levels.